Glucocorticoid levels predict subsequent social tactic in females of a facultatively social mammal. (28th December 2020) - Hill, Davina L.; Pillay, Neville; Schradin, Carsten
Abstract: Facultatively social species, in which individuals can switch between group‐ and solitary‐living tactics, offer an opportunity to shed light on proximate mechanisms underlying alternative life histories. Promising hormonal mediators of social tactic include glucocorticoids, which control energy allocation and are negatively related to body condition, and testosterone which regulates numerous social behaviours. Here, we investigated hormone profiles associated with social tactic in eight generations of free‐living female striped mice Rhabdomys pumilio . Females are group living during the non‐breeding season but live solitarily or with female kin in communally breeding groups during the breeding season. We tested whether females' baseline levels of corticosterone (a glucocorticoid) and testosterone measured during the breeding season differed before and after females left the group (i.e. when they switched from a group living to solitary social tactic), and whether the hormone levels of females that remained group living differed before and after their nestmates became solitary. We also asked whether seasonal variation in hormone levels was associated with social tactic. During the breeding season, corticosterone levels were lower in solitary than group‐living females both before and after solitary females left the group, and did not differ in solitary females before and after leaving. In group‐living females, corticosterone was higher after their nestmates became solitary than before they left. Testosterone levels did not differ before and after females became solitary and were not associated with social tactic. Corticosterone was higher during the breeding than the non‐breeding season in group‐living females but did not differ between the seasons in solitary females. Testosterone levels were higher in both social tactics during the non‐breeding season. We conclude that baseline corticosterone but not testosterone levels are associated with female social tactic, and that corticosterone levels at the start of the breeding season, when all females are group living, may be an indicator of subsequent tactic: solitary females' corticosterone levels were lower than those of females that remained group living even before the solitary phenotype was expressed. Glucocorticoids might therefore play a modulatory role in social organisation in facultatively social species. A free Plain Language Summary can be found within the Supporting Information of this article. Abstract : A free Plain Language Summary can be found within the Supporting Information of this article.